Explore the correlation between miR-338-5p and ZEB2 expression with clinical features as well as prognosis of Gastric Cancer (GC) - ahmed, yaser; WEI(MD), XIAOLI; ALAQILI (MDS), SAMAR; Sheng (Professor), ProDr. GU Kang (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Gastric cancer is the second leading cause of cancer-related death worldwide, with the highest incidence rate in Eastern Asia While surgery is primarily used for the treatment of early-stage gastric cancer, many patients develop advanced-stage cancers, or experience relapse after surgery, and therefore, require chemotherapy. Currently, cisplatin is one of the first-line chemotherapy drugs for gastric cancer. Unfortunately, initial cisplatin treatment frequently leads to recurrence of cancer, which unrelentingly retaliates with fast spreading and drug resistance Thus, the acquisition of cisplatin-resistance seriously hampers the effectiveness of chemotherapy, and is associated with poor patient prognosis and survival. Although some drugs have been applied in combination to cisplatin to gastric treatment cancer, the effectiveness of these regimens to counter chemoresistance is still limited, Therefore, it is imperative to elucidate how gastric cancer acquires cisplatin-resistance and develop therapeutic strategies to reverse chemoresistance. Epithelial-to-mesenchymal transition (EMT) has been associated with chemoresistance in various cancers. During EMT, cells lose cell-cell adhesions and gain cell-matrix interaction, acquiring traits linked to enhanced invasion and migration abilities. EMT also generates cancer stem cells (CSC), which are capable of initiating metastases in secondary organs. Recent research, provided additional evidence about the association between HOXA13 upregulation and gastric cancer progression. Also, it showed that HOXA13 contributes to invasion and EMT of gastric cancer cells via the TGF-β signaling pathway. The low expression of miR-195 played important roles in the pathogenesis and development of gastric cancer, possible by influencing the proliferation and growth of gastric cancer cells. In clinical practice, the detection of miR-195 played a certain role in guiding the treatment and prognosis of patients with gastric cancer. Reportedly, miR-138 sensitized NSCLC cells to ADM through regulation of EMT regulator ZEB2, these findings provided new insight into the mechanism responsible for the chemoresistance in human NSCLC and implied that miR-138 may serve as a potential the rapeutic candidate in drug-resistant NSCLC patients. Zinc finger E-box-binding homeobox 2 (ZEB2) is a transcription factor that intracellular promotes EMT by inhibiting E-Cadherin expression. It has been reported that ZEB2 overexpression is clinically associated with the poor survival of patients with colorectal cancer prostate cancer, pancreatic cancer, etc. It also maintains the stemness of cancer cells. Therefore, suppressing ZEB2 activation is a promising approach for suppressing cancer by inhibiting EMT. This possibly deprives cancer of chemoresistance. RNA interference using small interfering RNA (siRNA) is an effective method for gene silencing. These specifically designed double-stranded RNAs interfere the expression of target genes that possess a homologous sequence with the siRNAs. RNA interfering with siRNA has used to develop novel cancer therapies whereby conventional treatments lack efficacy. Previously, a lot of efforts have been devoted to silencing ZEB1 with siRNA, in which reversal of cancer EMT characteristics has been observed. This also holds promise to re-sensitize cancer cells to chemotherapy. Despite the functional role of ZEB2 has been revealed, few researches have focused on ZEB2 silencing in cancers, particularly gastric cancer. Herein we set force to explore the effectiveness of ZEB2 siRNA silencing to sensitize cisplatin-resistant human gastric cancer cells SGC7901/DDP. The silencing efficiency was evaluated and the effects on sensitivity to cisplatin and cell apoptosis were demonstrated in vitro. The results of this study justified the use of ZEB2 siRNA in combination with cisplatin to treat gastric cancer. This study was specifically designed to confirm the hypothesis that microRNA338-5p ( miR-338-5p) affects the development of cisplatin (DDP) resistance in human gastric cancer cells by targeting zinc finger E-box binding homeobox 2 (ZEB2). A total of 50 gastric cancer tissues and their corresponding normal adjacent tissue samples were collected. Then, the expression levels of miR-338-5p and ZEB2 in both gastric cancer specimens and cells were detected using the quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) and immunohistochemical methods. A dual‑luciferase reporter gene assay was conducted to evaluate the effect of miR-338-5p on the 3’-untranslated region (3’UTR) luciferase activity of ZEB2. SGC7901/DDP cells were transfected with miR-338-5p mimics and ZEB2 siRNA, respectively. Subsequently, changes in cellular proliferation and apoptosis were detected through the methyl thiazolyl tetrazolium assay and flow cytometric analysis, respectively. We also carried out a western blot analysis assay in order to detect the expression of apoptosis-related genes and ZEB2. miR-338-5p was significantly downregulated and ZEB2 was significantly upregulated in both gastric cancer tissues and SGC7901/DDP cells when compared with those in normal tissues and SGC7901 cells (P<0.01). The dual luciferase reporter gene assay showed that miR-338-5p could specifically bind with the 3’UTR of ZEB2 and significantly suppress the luciferase activity by 42% (P<0.01). Upregulation of miR-338-5p or downregulation of ZEB2 enhanced the sensitivity of SGC7901/DDP cells to DDP. miR-338-5p was significantly downregulated in both gastric cancer tissues and cells, while the expression of ZEB2 exhibited the opposite trend. Our study further demonstrated that miR-338-5p could enhance the sensitivity of SGC7901/DDP cells to DDP through targeted regulation of ZEB2 expression in gastric cancer tissues. CONCLUSION: The data further demonstrated that upregulation of miR-338-5p and downregulation of ZEB2 could increase the chemotherapeutic sensitivity of gastric cancer and chemotherapy-induced apoptosis. Collectively, all of these data suggest that miR-338-5p enhanced the sensitivity of gastric cancer to chemotherapy by directly targeting and regulating the expression of ZEB2. Thus, both miR-338-5p and ZEB2 exhibit great potential to serve as effective therapeutic targets for increasing the sensitivity of gastric cancer to DDP. The findings illustrated that miR-338-5p expression was significantly downregulated in gastric cancer, while ZEB2 expression exhibited the opposite trend. Moreover, ZEB2 was found to be a direct target of miR-338-5p. The upregulation of miR-338-5p or downregulation of ZEB2 could enhance the sensitivity of SGC7901/DDP cells to DDP-induced apoptosis and therefore miR-338-5p and ZEB2 can potentially regulate chemotherapy sensitivity through the apoptotic signaling pathway in gastric cancer patients.